Working on the Train? The role of technical Progress and the Trade in Explaining Wage Differentials in Italian Firms - Paolo Manasse; Luca Stanca (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
This paper presents firm-level evidence on the dynamics of the relative demand for non-manual workers in Italian manufacturing during the 1990s. The analysis provides a number of interesting results. First, the rise within firms in the share of non manual workers in both employment and hours worked (within-firm skill upgrading) is the main determinant of the increase in the relative demand for skilled workers. By contrast, demand changes associated to trade have mitigated such a rise by shifting employment away from skill-intensive firms. Second, while the relative number of hours worked by skilled workers within firms has risen, the hourly wage premium has fallen. Third, within-firm skill upgrading is strongly and significantly related to investment in computers and R&D. Fourth, we find that technical progress has raised the relative productivity of skilled workers (the skill-bias of technical progress is positive). Finally we show that the standard approach that measures annual, rather than hourly relative wages, produces a downward bias in the estimate of the skill-bias of technical progress.
Keywords: 330